2011
DOI: 10.1093/protein/gzr037
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cys38 knock-out and humanized version of NbAahII10 nanobody with improved neutralization of AahII Scorpion toxin

Abstract: During scorpion envenoming, highly toxic small polypeptides of the venom diffuse rapidly within the victim, causing serious medical problems. Nanobodies (Nbs), the recombinant single-domain antigen-binding fragments of camel-specific heavy-chain only antibodies, offer special advantages in therapy over classic antibody fragments due to their robustness and smaller size, matching the size of the scorpion toxins. Recently, a potent AahII scorpion toxin-neutralizing Nb was identified. However, this NbAahII10 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…The amino acid sequence analysis showed that NbAahII10 contains a single cysteine in its CDR1 (complementary-determining region 1) [17], which leads to dimerization of the Nb upon storage. To avoid this dimerization, the cysteine was substituted by serine and the resulting NbAahII10 C/S was shown to be identical to freshly prepared NbAahII10 in recognizing its cognate antigen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid sequence analysis showed that NbAahII10 contains a single cysteine in its CDR1 (complementary-determining region 1) [17], which leads to dimerization of the Nb upon storage. To avoid this dimerization, the cysteine was substituted by serine and the resulting NbAahII10 C/S was shown to be identical to freshly prepared NbAahII10 in recognizing its cognate antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Immunotherapy remains probably the most efficient treatment after envenomation, but the outcome depends on both accurate identification of the scorpion species involved and the timely anti-venom administration [16]. Because of their high affinity and specificity, small size and robust behaviour, the single-domain antibodies, referred to as Nbs (nanobodies), have been proposed to substitute the polyclonal Fab’ 2 to treat the scorpion envenoming [17,18]. Indeed, a bispecific Nb construct comprising an Nb neutralizing AahI’ toxin and an Nb neutralizing AahII toxin was proven to protect mice and rats that received a subcutaneous lethal dose of the scorpion venom [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fab' domain from equine IgG is 3 times larger than VHH domain from nanobodies, so its pharmacokinetics is more dynamic in nanobodies. For these reasons nanobodies have been reported to be very effective tools in addition to their ability to neutralize scorpions toxins rapidly (Hmila et al, 2008;Abderrazek et al, 2009Abderrazek et al, , 2011Hmila et al, 2010;Ezzine et al, 2012 Q5 ; Hmila et al, 2012). The advantage of using recombinant antibodies in general is directly linked to production yield and the ability to express antigen recognition domains only.…”
Section: Recombinant Antibodies Based Scorpion Antivenomsmentioning
confidence: 99%
“…A variety of antibody fragments against scorpion toxins has been produced and their capacity to neutralize the toxins in vitro and in vivo has been extensively tested [18][19][20][21][22][23][24][25][26][27]. As observed in other antigen-antibody systems, the in vivo neutralizing capacity of the anti toxin recombinant antibodies is influenced by the structural format of the molecule.…”
Section: Introductionmentioning
confidence: 99%